Implikasi Pendidikan Lingkungan Ramah Anak Terhadap Penguatan Karakter Siswa Madrasah Aliyah Negeri di Kota Bontang - Sultani, Sultani; Zamroni, (Al-Riwayah : Jurnal Kependidikan, 2024)
This research aims to determine the implications of child-friendly environmental education on strengthening the character of State Madrasah Aliyah students in Bontang City. In the current educational context, developing student character is the main focus in increasing the formation of individuals who are responsible and care about the environment. This study uses a qualitative research method with a field study approach, which involves participatory observation, interviews, and content analysis of various environmental education programs and activities carried out at the State Madrasah Aliyah in Bontang City. The research results show that child-friendly environmental education can make a positive contribution in strengthening students' character, especially in terms of environmental awareness, social concern and ethical values. These findings imply that child-friendly environmental education should be an integral part of the school curriculum, and a more holistic approach should be implemented to improve student character. The results of this research provide an important contribution to the debate about improving character education and its relevance in the context of Islamic education in Indonesia.